2015
DOI: 10.1037/a0038550
|View full text |Cite
|
Sign up to set email alerts
|

A brief history of the development of antidepressant drugs: From monoamines to glutamate.

Abstract: Major depressive disorder (MDD) is a chronic, recurring, and debilitating mental illness that is the most common mood disorder in the United States. It has been almost 50 years since the monoamine hypothesis of depression was articulated, and just over 50 years since the first pharmacological treatment for MDD was discovered. Several monoamine-based pharmacological drug classes have been developed and approved for the treatment of MDD; however, remission rates are low (often less than 60%) and there is a delay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
243
0
16

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 408 publications
(287 citation statements)
references
References 170 publications
0
243
0
16
Order By: Relevance
“…The glutamatergic dysfunction implicated in neural plasticity and cellular resilience may then contribute to the pathophysiology of depressive disorder, and riluzole was evaluated as a treatment for depression in both human and rodents [28]. A recent preclinical, observational, open-label study showed great improvement in the riluzole group compared to the placebo group [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…The glutamatergic dysfunction implicated in neural plasticity and cellular resilience may then contribute to the pathophysiology of depressive disorder, and riluzole was evaluated as a treatment for depression in both human and rodents [28]. A recent preclinical, observational, open-label study showed great improvement in the riluzole group compared to the placebo group [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Copersino et al retrospectively assessed cannabis withdrawal in a convenience sample of cannabis users and found that females endorsed significantly fewer instances of craving, increased sex drive, and greater instances of upset stomach compared to males [71]. More recently, Herrmann et al reported findings from a randomized clinical trial for the treatment of cannabis use disorder, and while males and females did not differ with regard to quantity of current cannabis use, females had significantly greater total withdrawal scores, endorsed a significantly higher incidence of withdrawal symptoms, and were more likely to experience irritability, violent outbursts, and nausea [19]. There was no difference between females and males on the average severity of individual withdrawal symptoms, however, among those who reported experiencing nervousness/anxiety, restlessness, or increased aggression during their last quit attempt, severity ratings of those symptoms were greater for females compared with males.…”
Section: The Status Of Findings For Sex Differences In Cannabis Withdmentioning
confidence: 99%
“…Recent work has called attention to the significance of sex differences in cannabis dependence and cannabis withdrawal [14]. Although cannabis use is more prevalent among males [1], females progress more rapidly from initial use to cannabis dependence [15, 16], exhibit worse treatment outcomes [17, 18], and experience greater withdrawal symptom severity [19]. Furthermore, evidence suggests that the endocannabinoid system, the primary neurobiological system implicated in cannabis withdrawal and cannabis reinforcement, is sexually dimorphic in nature [20] and may explain between-subjects variability in cannabis withdrawal [21].…”
Section: Introductionmentioning
confidence: 99%
“…It is often associated with major medical illnesses, such as cardiovascular disease, diabetes, and cancer, adding to their morbidity . Medications were first used as treatments for depression in 1958, and the first antidepressant medication to be marketed as such, imipramine, was introduced in 1959 . Since the 1980s, pharmacological treatment with antidepressant medications has been a major modality of therapeutic intervention in the management of depressive disorders .…”
mentioning
confidence: 99%